Financial Determinants of Firm Value In Indonesia’s Industrial Sector: The Moderating Role of Good Corporate Governance - Marseni Marseni; Fuad Ramdhan Ryanto (Economics and Business Journal (ECBIS), 2026)
This study analyzes the effect of Debt to Equity Ratio (DER), Return on Assets (ROA), and Asset Growth on Firm Value with Good Corporate Governance (GCG) as a moderating variable in industrial sector companies listed on the Indonesia Stock Exchange during the 2022–2024 period. The research method uses a quantitative associative approach with a sample of 65 companies and a total of 195 observations. The analysis technique used is Moderated Regression Analysis (MRA). The simultaneous test results show that DER, ROA, Asset Growth, GCG, and the moderating interaction variable have a significant effect on Firm Value with a significance value of 0.000 < 0.05. Partially, DER has a positive and significant effect on Firm Value, while ROA and Asset Growth do not have a significant effect on Firm Value. Good Corporate Governance has a positive and significant effect on Firm Value. Good Corporate Governance is able to moderate the effect of DER on Firm Value. Good Corporate Governance is not able to moderate ROA on Firm Value, and weakens the effect of Asset Growth on Firm Value